2020
DOI: 10.1111/cas.14334
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin suppresses bladder cancer growth via regulation of mechanistic target of rapamycin pathway

Abstract: Luteolin is a natural flavonoid with strong anti-oxidative properties that is reported to have an anti-cancer effect in several malignancies other than bladder cancer. In this study, we describe the effect of luteolin on a human bladder cancer cell line, T24, in the context of the regulation of p21, thioredoxin-1 (TRX1) and the mechanistic target of rapamycin (mTOR) pathway. Luteolin inhibited cell survival and induced G2/M cellcycle arrest, p21 upregulation and downregulation of phospho(p)-S6, which is downst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…Caused cell cycle arrest [362,[374][375][376][377]. Decreased cell viability and proliferation [378][379][380][381][382][383].…”
Section: Luteolinmentioning
confidence: 99%
See 1 more Smart Citation
“…Caused cell cycle arrest [362,[374][375][376][377]. Decreased cell viability and proliferation [378][379][380][381][382][383].…”
Section: Luteolinmentioning
confidence: 99%
“…Bladder cancer cell survival was inhibited by luteolin by inducing G2/M cell cycle arrest, p21 upregulation and inhibition of mTOR signalling. In xenograft models, tumor volumes and dimensions were decreased after oral administration of luteolin [377]. When combined with the anticancer agent oxaliplatin, luteolin inhibited gastric cancer cell proliferation and induced apoptosis through the cytochrome-c and caspase pathways and by altering the cell cycle [391].…”
Section: Luteolinmentioning
confidence: 99%
“…Decreased PI3K, AKT, and mTOR phosphorylation were also observed in human breast cancer cells at 50 µM for 48 h [ 210 ]. Remarkably, Myricetin [ 241 , 242 ], Apigenin [ 243 , 244 ] and its derivative Vitexin [ 206 , 207 ], Luteolin [ 226 , 228 , 245 ], Eriotyctiol [ 62 , 209 ], Taxifolin [ 216 , 246 , 247 ], Naringenin [ 248 , 249 ], EGCG [ 215 , 250 , 251 ], and Cyanidin [ 252 , 253 , 254 ] also decreased AKT phosphorylation and mTOR effectors in several cancer models, avoiding this feedback activation loop.…”
Section: Flavonoids and Cell Growth Signalingmentioning
confidence: 99%
“…The Akt/mTOR signaling is essential for the proliferation, metabolism and angiogenesis [31]. Studies have reported that inhibition of mTOR effectively suppressed tumor growth in several cancers, including bladder [32], breast [33], pancreatic [34,35], and colon [6,9] cancers. mTORC1 and mTORC2 are the two different complexes of mTOR.…”
Section: Discussionmentioning
confidence: 99%